Characterization of the inflammatory response in the central nervous system of mice susceptible or resistant to demyelination by Theiler's virus. - Mark D. Lindsley; Moses Rodriguez (1989)
Intracerebral inoculation of mice with Theiler's murine encephalomyelitis virus results in an intense inflammatory response of mononuclear leukocytes which infiltrate into the central nervous system. Resistant strains of mice have the ability to clear virus whereas susceptible strains become infected persistently and are associated with chronic demyelination which is proposed to be immune-mediated. In an attempt to better understand the role of the immune response during demyelination, mononuclear leukocytes were isolated from the central nervous system of infected mice and stained by an immunoperoxidase technique with anti-Thy-1.2, anti-L3T4, anti-Lyt-2 and anti-MAC-1 mAb. Infection of susceptible SJL/J mice resulted in a biphasic immune response which peaked on days 7 and 27 post-infection. In contrast, a single peak (day 7) was observed in resistant C57BL/10SNJ mice. The presence of Thy-1.2, L3T4, and MAC-1+ cells was similar between the two strains. However, although the number of Lyt-2+ cells peaked on day 7 in C57BL/10SNJ mice, they were not detected in SJL/J mice until 14 days post-infection and gradually increased in number over the course of infection. To further study the role of T cells in demyelination, serial frozen sections of brain and spinal cord were stained for the presence of Lyt-2 and L3T4+ cells in the lesions of chronically infected SJL/J mice. L3T4+ cells were observed predominantly in perivascular regions while Lyt-2+ cells were observed infiltrating the parenchyma. These results provide further evidence that Lyt-2+ lymphocytes are important in the mechanism of susceptibility/resistance to Theiler's murine encephalomyelitis virus-induced demyelination.